Reconstruction of Subduction and Back‐Arc Spreading in the NW Pacific and Aleutian Basin: Clues to Causes of Cretaceous and Eocene Plate Reorganizations. Issue 4 (17th April 2019) - Vaes, Bram; van Hinsbergen, Douwe J. J.; Boschman, Lydian M.
Abstract: The Eocene ( 50–45 Ma) major absolute plate motion change of the Pacific plate forming the Hawaii‐Emperor bend is thought to result from inception of Pacific plate subduction along one of its modern western trenches. Subduction is suggested to have started either spontaneously, or result from subduction of the Izanagi‐Pacific mid‐ocean ridge, or from subduction polarity reversal after collision of the Olyutorsky arc that was built on the Pacific plate with NE Asia. Here we provide a detailed plate‐kinematic reconstruction of back‐arc basins and accreted terranes in the northwest Pacific region, from Japan to the Bering Sea, since the Late Cretaceous. We present a new tectonic reconstruction of the intraoceanic Olyutorsky and Kronotsky arcs, which formed above two adjacent, oppositely dipping subduction zones at 85 Ma within the north Pacific region, during another Pacific‐wide plate reorganization. We use our reconstruction to explain the formation of the submarine Shirshov and Bowers Ridges and show that if marine magnetic anomalies reported from the Aleutian Basin represent magnetic polarity reversals, its crust most likely formed in an 85‐ to 60‐Ma back‐arc basin behind the Olyutorsky arc. The Olyutorsky arc was then separated from the Pacific plate by a spreading ridge, so that the 55‐ to 50‐Ma subduction polarity reversal that followed upon Olyutorsky‐NE Asia collision initiated subduction of a plate that was not the Pacific. Hence, this polarity reversal may not be a straightforward driver of the Eocene Pacific plate motion change, whose causes remain enigmatic. Key Points: At 85‐80 Ma, a plate reorganization occurred in the northern Pacific that included the formation of two subduction zones and the Kula plate Our reconstruction predicts that the Aleutian Basin crust formed between 85 and 60 Ma in a back‐arc basin behind the Olyutorsky arc Subduction polarity reversal from Kamchatka to Sakhalin at 50 Ma is not a straightforward driver of the Eocene Pacific plate motion change